APLIKASI PEMBELAJARAN SEJARAH KELAS XI SEMESTER I BERBASIS WINDOWS PHONE - Dody Pradana; Erfanti Fatkhiyah; Rr. Yuliana Rachmawati (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
The application ofhistory learning for 1st semesterclass xi based on windows phone which is develop for helping learning procces of student and other people about history espesially history of Indonesia. This application is developed based on mobile application which can use on handphone or smartphone with windows phone operating system. This application is develop with C# language with SQLite for storage database. This application is a simple game with focus to questions about history of Indonesia. The game is divided into two part there are text and picture. This application also have a history theory as a part of learnnig.